Etude séroépidémiologique du paludisme au Sahara algérien. - Benzerroug, E. H. (World Health Organization, 1991)
On the basis of geoclimatic characteristics, the Saharan region of Algeria (area, 2 million km2) is made up of several subregions; analysis of the historical data on malaria in this region seems to show that the epidemiological situation is closely linked to climatic and hydrographic conditions. A longitudinal sero-epidemiological study was conducted in this vast region from September 1983 to April 1985. The general findings do not appear to support the existence of active foci of transmission, but analysis of the data for certain oases and localities leads to a quite different assessment of the epidemiological situation. At Ouargla, for example, the serological results obtained by indirect immunofluorescence show prevalence of under 5% in the four successive surveys, whereas in Heïha oasis over 50% of subjects over 30 years of age were found to be seropositive. The results of the longitudinal seroepidemiological surveys conducted in a number of localities and oases in the Saharan region reflect the diversity of epidemiological settings and provide evidence that there is low-level malaria transmission in some oases such as Heïha, Yakou, Ihérir and probably in In-Salah. These surveys confirm that malaria transmission has been halted in the former foci such as Ouargla and Timimoune. Finally, the longitudinal sero-epidemiological study shows there are movements of potential parasite carriers from countries south of the Sahara and therefore that oases associated with trans-Saharan trade are vulnerable.